Influence of standard modifiable risk factors on ventricular tachycardia after myocardial infarction - Deshmukh, Tejas; Kovoor, Joshua G.; Byth, Karen; Chow, Clara K.; Zaman, Sarah; Chong, James J. H.; Figtree, Gemma A.; Thiagalingam, Aravinda; Kovoor, Pramesh (Frontiers in Cardiovascular Medicine, 2023)
Background Inducible ventricular tachycardia (VT) at electrophysiology study (EPS) predicts sudden cardiac death because of ventricular tachyarrhythmia, the single greatest cause of death within 2 years after myocardial infarction (MI). Objectives We aimed to assess the association between standard modifiable risk factors (SMuRFs) and inducible VT at EPS early after MI. Methods Consecutive patients with left ventricle ejection fraction ≤40% on days 3–5 after ST elevation MI (STEMI) who underwent EPS were prospectively recruited. Positive EPS was defined as induced sustained monomorphic VT cycle length ≥200 ms for ≥10 s or shorter if hemodynamically compromised. The primary outcome was inducibility of VT at EPS, and the secondary outcome was all-cause mortality on follow-up. Results In 410 eligible patients undergoing EPS soon (median of 9 days) after STEMI, 126 had inducible VT. Ex-smokers experienced an increased risk of inducible VT [multivariable logistic regression adjusted odds ratio (OR) 2.0, p = 0.033] compared with current or never-smokers, with comparable risk. The presence of any SMuRFs apart from being a current smoker conferred an increased risk of inducible VT (adjusted OR 1.9, p = 0.043). Neither the number of SMuRFs nor the presence of any SMuRFs was associated with mortality at a median follow-up of 5.4 years. Conclusions In patients with recent STEMI and impaired left ventricular function, the presence of any SMuRFs, apart from being a current smoker, conferred an increased risk of inducible VT at EPS. These results highlight the need to modify SMuRFs in this high-risk subset of patients.